1966
DOI: 10.1063/1.1728098
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Activation and Nonequilibrium Unimolecular Reactions of C2H5Cl and 1,2-C2H4Cl2 Molecules

Abstract: A gas-phase chemical activation technique employing the H and Cl abstraction reactions by methylene from chloromethanes has been developed for the production of chloroethanes in the energy range between 85 and 95 kcal mole−1. In this paper the results from the reaction of methylene with chloromethane are reported. The abstraction reactions serve as a clean source of methyl and chloromethyl radicals; combination of these radicals at 25°C produces C2H5Cl and 1,2-C2H4Cl2 at energies near 90 kcal mole−1. Since the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1968
1968
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…(5) ch4 kcal/mol, as suggested by Hassler and Setser (1966). This increased the relative importance of reaction 2 with respect to the other channels and rendered the HC1 elimination process as the major reaction pathway above 1200 K, which appears more plausible in view of the experimental data on the CCOP process (Granada et al, 1987).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…(5) ch4 kcal/mol, as suggested by Hassler and Setser (1966). This increased the relative importance of reaction 2 with respect to the other channels and rendered the HC1 elimination process as the major reaction pathway above 1200 K, which appears more plausible in view of the experimental data on the CCOP process (Granada et al, 1987).…”
Section: Resultsmentioning
confidence: 87%
“…It must be noted that the experimental and detailed RRKM (Rice-Rampsperger-Kassel-Marcus) analysis of chemically activated recombination reactions of CH2C1 and CH3 at low temperatures, when only one decomposition channel is accessible, exists (Hassler and Setser, 1966;Hassler et al, 1966). However, with the exception of a brief note by Tavakoli and Bozzelli (1987), we are not aware of 0888-5885/88/ 2627-0447$01.50/0 such studies at higher temperatures under which multiple decomposition channels become accessible to the chemically activated adducts.…”
mentioning
confidence: 99%
“…The decomposition of 1,2-dichloroethane (1,2-DCE) has received enormous attention over the last five decades. The literature on this reaction can be arbitrarily divided into fundamental and applied studies. All the “applied” studies concern themselves with improving the production of the vinyl chloride, which is the raw material for the manufacture of the industrially important poly(vinyl chloride), PVC.…”
Section: Introductionmentioning
confidence: 99%
“…(The activation energy and barriers are given in kcal mol -1 here and throughout the paper). Setser and co-workers assumed that the HCl elimination barrier from 1,2-DCE would be equal to that of EC, but cautioned that it may be a lower limit . In fact, Dees and Setser 6 later on suggested that the HCl elimination barrier for 1,2-DCE should be higher than that of EC.…”
Section: Introductionmentioning
confidence: 99%
“…Hassler et al [16] considered falloff behavior for reaction R1 and pointed out that, at 1.3 atm, this reaction is in highpressure limit at 600-1500 K. Kara and Senkan [17] have analyzed the falloff behavior of CH 2 Cl + CH 2 Cl from 0.5 atm up to 10 atm and T = 500-1700 K. They pointed out the lack of experimental data on the falloff behavior of reaction R1 and cautioned that their results await experimental verification. Incavo [9] studied 1,2-dichloroethane cracking to vinyl chloride in the presence of CCl 4 and Cl 2 at 500 K. He reported different byproducts including methyl chloride and methylene chloride.…”
Section: Introductionmentioning
confidence: 99%